The helicoidal Hubbard model - Gouveia, José Daniel Lago da Silva Neves (2013)
The Hubbard model is one of the most simple models to describe the motion and interaction of electrons in solids. It has been widely studied due to its applications in the description of organic conductors and in the search for high Tc superconductivity. In this work, the Hubbard model in a helicoidal lattice is studied, a lattice identical to the two-dimensional square lattice in the thermodynamic limit. The magnetic phases of this model are analyzed by building mean eld phase diagrams. The thermodynamics of this model is studied in the strong coupling limit (U ! 1). We consider hoppings along and across helix steps. The hoppings across helix steps generate a mixing of the spin con gurations, whose dynamics is also studied.